Mathematical Study On Predator-Prey Holling Type-Ii Effect Of Fading Memory - et. al., L. Sahaya Amalraj, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we investigate the effect of Fading Memory on Predator-Prey Holling Type-II model which was previously developed. We obtain approximate analytical solution to the dimensionless prey and predator population, using the new approach to Homotopy perturbation method. The analytical solution is discussed graphically and compared with the previous study and found to be in good agreement.